Preparation and characterisation of novel paddy cultivation herbicide nanocomposite from zinc/aluminium layered double hydroxide and quinclorac anion. (29th July 2019) - Sharif, Sharifah Norain Mohd; Hashim, Norhayati; Md Isa, Illyas; Ali, Noorshida Mohd; Bakar, Suriani Abu; Hussein, Mohd Zobir; Mamat, Mazidah; Bakar, Norlaili Abu; Mahamod, Wan Rusmawati Wan
Abstract: Zn/Al-layered double hydroxide-quinclorac (Zn/Al-LDH-QC) nanocomposite has been synthesised via co-precipitation method. The versatility of the Zn/Al-LDH enables this host material to be intercalated with quinclorac (QC), a type of auxin agonist herbicide that was widely used in paddy cultivation. The PXRD analysis shows that the basal spacing of the Zn/Al-LDH-QC nanocomposite expanded in the range of 15.8–16.7 Å (from 8.8 Å in Zn/Al-LDH), therefore indicating the successful intercalation of QC into the interlayer gallery of Zn/Al-LDH. The intercalation was also proven from the FTIR and elemental analysis. The thermogravimetric analysis conducted using TGA/DTG shows that the Zn/Al-LDH-QC exhibits better thermal stability compared to the pure QC herbicide. Based on the results collected from the ICP-OES, CHNS analyser, and TGA/DTG, the chemical formula of Zn/Al-LDH-QC was proposed as [Zn0.75 Al0.25 (OH)2 ][C9 H4 Cl2 NCOO] − 0.25 0.90H2 O. This study shows that the Zn/Al-LDH has potential to be used as a host material for herbicide in paddy cultivation sector.